2010
DOI: 10.1007/s10681-010-0298-5
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology as fertility predictor in hybrid tea roses

Abstract: Fertility of hybrid tea roses is often reduced due to their interspecific origin but also to intensive inbreeding. New genotypes used as pollen donors represent an economic risk for a breeding programme, as their influence on seed production is unknown. In this study 11 cut rose genotypes were selected from a company database as high fertile or low fertile male parents, according to the number of seeds per hybridisation. Pollen morphology and in vitro germination of the selected genotypes were characterised. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Unlike many other cultivated plant species (Kilian et al, 2007; Gil-Ariza et al, 2009; Wang et al, 2010; Gross et al, 2014), we did not see a reduction over time when we considered the year of release of the variety. This may corroborate observations on the sensitivity of rose for inbreeding depression, which makes selfing unsuitable as a breeding strategy (Pipino et al, 2011). It might also be the result of the large range of ornamental traits that breeders have selected for, causing selection to never be consistently in the same direction.…”
Section: Discussionsupporting
confidence: 86%
“…Unlike many other cultivated plant species (Kilian et al, 2007; Gil-Ariza et al, 2009; Wang et al, 2010; Gross et al, 2014), we did not see a reduction over time when we considered the year of release of the variety. This may corroborate observations on the sensitivity of rose for inbreeding depression, which makes selfing unsuitable as a breeding strategy (Pipino et al, 2011). It might also be the result of the large range of ornamental traits that breeders have selected for, causing selection to never be consistently in the same direction.…”
Section: Discussionsupporting
confidence: 86%
“…Some literatures have postulated that figs control seed loss though variation in style length [1418]. In some plants such as fig ( Ficus maxima ), it is believed that stigma length shows an allometric relationship with style length.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in pollen viability and germination rate during storage at -20 °C For this study, five cultivars ('Golden Fashion', 'Dolphin', 'Swan', 'Touch of Class', 'New Fashion') with high fertility pollen, based on their diameter larger than 30 µm (Pipino et al 2011b), were selected; these cultivars were also suggested by NIRP International, provider of the used material, as cultivars with high potential for breeding programs. The pollen aspect during TTC coloration and pollen grain germination is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%